Original articleHDR brachytherapy as a solution in recurrences of locally advanced prostate cancer - Łyczek, Jarosław; Kawczyńska, Maria M.; Garmol, Darek; Kasprowicz, Anetta; Kulik, Anna; Dąbkowski, Mateusz; Czyżew, Beata; Gruszczyńska, Ewelina; Bijok, Michał; Kowalik, Łukasz (Journal of Contemporary Brachytherapy, 2009)
Purpose: The object of this study was to analyze the outcome of salvage HDR brachytherapy treatment after local failure, for patients with prostate specific antigen (PSA) failure without distant metastasis, after external beam radiation and HDR brachytherapy treatment, or after radical prostatectomy, with or without hormonal therapy. Material and methods: The group of 115 patients, without distant metastasis, after local failure and external beam radiation, followed by HDR brachytherapy treatment, or after radical prostatectomy, with hormonal therapy and without, have been enrolled to salvage HDR brachytherapy (SBR). All patients had minimum 3 months androgen deprivation therapy before salvage brachytherapy, which was continued until the next 9 months after SBR. Brachytherapy was administered in three 10 Gy fractions with 3 weeks gap between them. Each session of SBR was supported by trans-rectal USG real time pictures. The treatment planning was done on the base of Abacus system from Sauerwein® or with SWIFT system from Nucletron®. The following data were collected: Gleason score, clinical staging, the volume of the prostate, PSA before and after the initial treatment and periodically during the follow-up period. Also the time during which the PSA stays at the nadir level, patient’s age and toxicity of treatments were taken into consideration. Results: Doses from external radiotherapy or from HDR brachytherapy were recalculated to equivalent biological dose (EBD). The independence from biochemical progression in our group of patients after retreatment was 46% for patients with PSA Ł 6 and 18% for patients with PSA > 6. Overall survival for patients with PSA Ł 6 was 86% and 48% for patients with PSA > 6, respectively. Conclusions: Salvage prostate brachytherapy (SBR) can be safely performed with acceptable biochemical control and toxicity.